Свойства коммутационных ячеек, используемых в системах автоматизированного контроля - Medvedik, A. D. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The main properties of switching cells with an arbitrary number of outputs are considered, on the basis of which regular switching structures are constructed. The total number of all possible connections between outputs for a given number of independent connections is determined, as well as the maximum possible number of non-repeating connections for the same conditions. The minimum number of switching elements required to satisfy the connection completeness condition has been determined. A comparative analysis of known switching structures has been carried out.